(untitled) (Research, Society and Development, 2021)
With the pandemic of COVID-19, and the social distancing imposed by it, there was the need to develop strategies for the teaching-learning process to be maintained. Thus, concepts such as ubiquitous learning and mobile learning have started to appear among students, professors, and the entire academic community, including dentistry courses. Thus, the understanding of these non-traditional forms of learning becomes necessary, so that their application can be done in a responsible way. The objective of this work was to characterize mobile and ubiquitous learning and its applications in dentistry. An integrative literature review was conducted using the PubMed and Scielo databases. The search strategy considered the terms: "mobile learning and dentistry" "ubiquitous learning and dentistry" and their corresponding terms in English "mobile learning and dentistry", over a period of 10 years (2011 to 2021). The descriptive analysis, in the light of the national and international scientific literature, allowed grouping a sample of eight articles with scientific evidence to characterize mobile and ubiquitous learning and its applications in dentistry, identify which tools are used for this purpose and their impact on the teaching-learning process. Based on the above, the new reality imposed and accelerated by the COVID-19 pandemic, regarding the use of digital teaching-learning tools, especially mobile and ubiquitous learning, is possible and has already proven to be effective, especially when associated with face-to-face meetings, although further studies are needed to verify its direct impacts on students and teachers.